2017
DOI: 10.1007/s10096-017-2906-y
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-ToF short incubation identification from blood cultures is associated with reduced length of hospitalization and a decrease in bacteremia associated mortality

Abstract: The purpose of this study was to assess the impact of MALDI-ToF identification and rapid short incubation MALDI-Tof identification protocol on patient care compared to conventional identification. By using a retrospective review we assessed the impact of a rapid Bruker MALDI-Tof identification protocol. Overall there was a 16.76-hour reduction in time to identification of the pathogen after the introduction of MALDI-TOF identification in 2013 (P<0.0001) and a further 15-hour reduction (P<9.37 E-05) after imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…Adjustments in antimicrobial therapy after initial empirical therapy may result in better outcomes 25,26 . Huang et al 12 , Perez et al 5 and Delport et al 13 observed that reduction in time to identify microorganism resulted in rapid adjustments in antimicrobial treatment, however, as highlighted, the This work has some limitations. Data were collected in a single unit from a single institution, reducing the generalizability of the findings.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Adjustments in antimicrobial therapy after initial empirical therapy may result in better outcomes 25,26 . Huang et al 12 , Perez et al 5 and Delport et al 13 observed that reduction in time to identify microorganism resulted in rapid adjustments in antimicrobial treatment, however, as highlighted, the This work has some limitations. Data were collected in a single unit from a single institution, reducing the generalizability of the findings.…”
Section: Discussionmentioning
confidence: 97%
“…However, among the outstanding advantages, we observed some discrepancies with our data. However, an important difference observed is the automated microbiological identification method used by Huang et al 12 , Perez et al 5 and Delport et al 13 : matrix assisted laser desorption ionization-time of flight (MALDI-TOF). This methodology is technically superior to the VITEK® 2 compact 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al valorar las variables clínicas y laboratoriales que inciden en la mortalidad en niños con (BAC), en relación a la edad, si bien la presencia de (BAC) fue significativamente mayor en los menores de 5 años de edad, la mortalidad fue semejante en ambos grupos (p=0,8), al establecer la relación entre las demás variables, la presencia de desnutrición, la infección a múltiples focos, la presencia de choque al ingreso, Glasgow <12, Saturación de Oxígeno menor a 94%, anemia severa y bacteriemia por Gram positivos se asociaron significativamente a mortalidad en la presente serie; siendo la mortalidad de la misma 16,5% similar a la mortalidad por (BAC) registrada en Estados Unidos y Europa 15 a 22% y menor a la mortalidad registrada en otros Países de (15,16,5) Latinoamérica 28 a 40%…”
Section: Conforme Al Presente Estudio Del Instituto Deunclassified
“…In addition, combined with antimicrobial stewardship team intervention, it has been shown to be cost-effective (Patel et al, 2016;Perez et al, 2013). MALDI-TOF analysis combined with a short subculture time of positive blood cultures (si-MALDI-TOF) is an improvement of this technique, allowing even shorter time to pathogen identification with a positive effect on antibiotic therapy (Idelevich et al, 2014;Kohlmann et al, 2015), and is also associated with reduced length of hospital stay and mortality in patients with BSI (Delport et al, 2017).…”
Section: Introductionmentioning
confidence: 99%